A study on the prevalence of chronic obstructive pulmonary disease among adults in Madurai, Tamil Nadu - Saleem, Mohamed; Priya, Sivasubramanian; Pradeep, Manimaran; Sabeetha, Kalifulla (International Journal Of Community Medicine And Public Health, 2017)
Background: Chronic obstructive pulmonary disease (COPD) is a major public health problem with increasing prevalence especially in developing countries. Burden of disease estimation is important for decision making, planning, prioritising and allocating funds. It has been found that the recent data on prevalence of COPD is less in south India, especially Tamil Nadu. Hence this study was undertaken in order to estimate the prevalence of COPD in Madurai among adults and its association with socio demographic variables. Methods: This is a community based cross-sectional study done in Kallendiri block of Madurai district with adults aged >30 years of both the sexes as study population. Sample size was 480. Using cluster sampling method, study participants were interviewed with semi-structured questionnaire and peak expiratory flow rate was measured using peak flow meter. Results: Prevalence of COPD was 22.1% among the study population. Males (39.2%) had higher prevalence than females (12.2%). COPD prevalence was significantly higher among increasing age, male sex, illiteracy, low BMI, smokers, inadequate ventilation and those using biomass fuels for cooking. Conclusions: This study has established the fact that COPD is highly prevalent among adults in rural area. For practitioners, the results call for a high index of suspicion of COPD among >30 years with substantial exposure to risk factors. For health policy makers, the results of the current study urge for the development of COPD prevention programs failing which the burden of COPD might result in increased mortality, morbidity and economic burden.